ANALISIS PROMOSI CASHBACK PADA E-COMMERCE BUKALAPAK DALAM PERSPEKTIF EKONOMI SYARIAH - Edi Jatmiko; Siti Kholijah; Fitri Utami (LPPM STAI DARUSSALAM LAMPUNG, 2023)
Online shopping in e-commerce has become a habit of Indonesian people, this trend started with the Covid-19 pandemic. There are various factors that motivate Indonesian consumers to shop online. One of them is a cashback promotion. This research method uses library research. The results of this research are that cashback is often considered a marketing strategy that aims to attract customer attention. This cashback practice can be classified as khiyar ghabn in the context of Islamic law. The function of khiyar in buying and selling transactions is to provide the ability for the transacting parties to consider long-term consequences in order to avoid regrets in the future. Thus, it can be said that cashback is permitted because it is a form of deception aimed at persuading customers, as implemented in platforms such as bukalapak. Cashback is considered permissible because it does not involve elements of usury and is included in the khiyar ghabn category.